The role of short films in vocabulary and cultural learning in the Spanish language classroom in Ghana: A learner-centred perspective - Ofori, Josephine Araba Duncan; Kabio-Danlebo, Franklina (Revista Cedotic, 2025)
Recent pedagogical research highlights the benefits of using films in the language classroom to expose learners to authentic language use and cultural perspectives, which traditional resources like textbooks may not provide. While full-length films may pose challenges such as time constraints and student disengagement, short films accessible through digital platforms like YouTube and TikTok offer a practical solution to these challenges. This study explored the impact of using short films asan alternative pedagogical tool for vocabulary and cultural learning in the class room, exploring the experiences of Spanish students at the University of Ghana. The findings showed that short films effectively enhance vocabulary and cultural understanding, with students favouring comedy, educational, and romantic genres. The results provide language educators with valuable insights into the effective use El presente estudio examinó el impacto del uso de cortometrajes como recurso pedagógico alternativo para la adquisición de vocabulario y el aprendizaje cultural en el aula, tomando como referencia las experiencias de los estudiantes de español de la Universidad de Ghana. Los resultados evidenciaron que los cortometrajes contribuyen de manera significativa a la ampliación del vocabulario y al fortalecimiento de la comprensión cultural, siendo los géneros de comedia, educativos y románticos los más valorados por los estudiantes. En consecuencia, los hallazgos ofrecen a los docentes de lenguas extranjeras aportes relevantes sobre la utilización eficaz de los cortometrajes como recurso pedagógico, al constituir una herramienta práctica y motivadora para favorecer simultáneamente la adquisición léxica y la competencia intercultural en la enseñanza y aprendizaje del español como lengua extranjera.